(untitled) - Cullity, B. D. (Upper Saddle River, New Jersey, 2001)
Intended to acquaint the reader with the theory of x-ray diffraction, the experimental methods involved, and the main applications. The book is a collection of principles and methods stressing X-ray diffraction rather than metallurgy. The book is written entirely in terms of the Bragg law and can be read without any knowledge of the reciprocal lattice. It is divided into three main parts—Fundamentals; experimental methods; and applications. Designed for beginners, not as a reference tool for the advanced reader.
Keywords: X-rays; Difraction